Efficacy of fungicides in control of turmeric leaf spot caused by Colletotrichum capsici at Tepi, Southwestern Ethiopia - Jibat, Merga; Asfaw, Mulukan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
Turmeric leaf spot, caused by the pathogen Colletotrichum capsici, is the greatest damaging disease that limits the production and productivity of turmeric, and reduces qualitative and quantitative rhizome yields in Southwestern Ethiopia. A field trial was conducted to evaluate the efficacy of different fungicides against a disease epidemic of turmeric leaf spot in Southwestern Ethiopia. The field experiment was performed at Tepi Agricultural Research Center during the 2019 and 2020 main cropping seasons using four fungicides: Ethiozeb 80% WP (mancozeb), Prozole 255 EC (propiconazole), Mancolaxyl 72% WP (mancozeb + metalaxyl) and Ridomil Gold MZ 68 WG (metalaxyl-M), which were applied either as seed rhizome treatments plus foliar spray, or as foliar spray alone for control of leaf spot infection. The field experiment was laid out in a randomized complete block design with nine treatments and three replications. The results of the experiment indicated that both rhizome treatment + foliar spray, and foliar fungicide spray treatments significantly affected the turmeric leaf spot epidemics. The effect of the foliar spray Prozole 255 EC (propiconazole) was significantly higher than the other treatments in reducing disease severity (27.0) and maximizing rhizome fresh yield (34.1 ton/ha). The maximum cost benefit ratio (1:2.65) was achieved by the foliar spray fungicide Prozole 255 EC (propiconazole). Amongst different fungicides considered, the foliar spray Prozole 255 EC (propiconazole) reduced leaf spot disease incidence up to 47.1% over the control onthe last day of disease evaluation. The whole outcome of this experiment showed that foliar Prozole 255 EC (propiconazole) fungicide sprays were effective in alleviating the epidemic of turmeric leaf spot and boosting turmeric production and productivity.
Keywords: Colletotrichum capsici; turmeric; fungicides; yield; Ethiopia